Enhancing Law Enforcement Effectiveness in Addressing Land Mafia Practices to Safeguard Community Land Rights - Mamanda Syahputra Ginting; Erna Dewi; Muhammad Amin; Fristia Berdian Tamza; Thearizky Ahmad (Faculty of Law, Universitas Lampung, 2025)
This research examines the pervasive issue of land mafia practices in Indonesia, which pose significant threats to land rights and contribute to broader economic, social, and legal challenges. Employing a normative legal research methodology, the research evaluates the implementation of preventive and law enforcement measures, with particular focus on Ministerial Regulation No. 15 of 2024, which establishes a legal framework for addressing land disputes. The research underscores the One Map Policy as a crucial initiative for enhancing transparency and integrating land-related data to mitigate fraudulent activities. By assessing the effectiveness of existing policies and identifying key challenges, this research offers recommendations to strengthen law enforcement, inter-agency coordination, and public participation. The findings emphasize that a comprehensive, multi-stakeholder approach is imperative for eradicating land mafia practices, ensuring legal certainty, and safeguarding community land rights.